PENGARUH ORIENTASI TUJUAN TERHADAP ADAPTABILITAS KARIER YANG DIMEDIASI OLEH EFIKASI DIRI PADA MAHASISWA S1 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Ridha Fitri; Megawati Megawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
This study aims to determine the effect of goal orientation on career adaptability mediated by self-efficacy in undergraduate students at the Faculty of Economics and Business, Syiah Kuala University. This research is a quantitative research. The sample used in this study were 247 college students who were selected through a proportionate stratified random sampling technique. Data were collected through questionnaires and analyzed using Partial Least Square (PLS). Based on the results of the analysis, it shows that goal orientation influences career adaptability. Goal orientation influences self-efficacy. Self-efficacy influences career adaptability. Self-efficacy mediates the relationship between goal orientation and career adaptability.